Inhibition of HLA-DQ2 Mediated Antigen Presentation by Analogues of a High Affinity 33-Residue Peptide from α2-Gliadin - Xia, Jiang (2006)
Human leukocyte antigen DQ2 is a class II major histocompatibility complex protein that plays a critical role in the pathogenesis of Celiac Sprue by binding to epitopes derived from dietary gluten and triggering the inflammatory response of disease-specific T cells. Inhibition of DQ2 mediated antigen presentation in the small intestinal mucosa of Celiac Sprue patients therefore represents a potentially attractive mode of therapy for this widespread but unmet medical need. Starting from a pro-inflammatory, proteolytically resistant, 33-residue peptide, LQLQPFPQPELPYPQPELPYPQPELPYPQPQPF, we embarked upon a systematic effort to dissect the relationships between peptide structure and DQ2 affinity, and to translate these insights into prototypical DQ2 blocking agents. Three structural determinants within the first 20 residues of this 33-mer peptide, including a PQPELPYPQ epitope, its N-terminal flanking sequence and a downstream Glu residue, were found to be important for DQ2 binding. Guided by the X-ray crystal structure of DQ2, the L11 and L18 residues in the truncated 20-mer analogue were replaced with sterically bulky groups so as to retain high DQ2 affinity but abrogate T cell recognition. A dimeric ligand, synthesized by regiospecific coupling of the 20-mer peptide with a bifunctional linker, was identified as an especially potent DQ2 binding agent. Two such ligands were able to attenuate the proliferation of disease-specific T cell lines in response to gluten antigens, and therefore represent prototypical examples of pharmacologically suitable DQ2 blocking agents for the potential treatment of Celiac Sprue.